1997
DOI: 10.1002/(sici)1099-0488(199702)35:3<523::aid-polb11>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of polydimethylsiloxane swollen with supercritical carbon dioxide

Abstract: Viscosity curves were measured for polydimethyl siloxane (PDMS) melts swollen with dissolved carbon dioxide at 50 and 80ЊC for shear rates ranging from 40 to 2300 s 01 , and for carbon dioxide contents ranging from 0 to 21 wt %. The measurements were performed with a capillary extrusion rheometer modified for sealed, highpressure operation to prevent degassing of the melt during extrusion. The concentration-dependent viscosity curves for these systems are self-similar in shape, exhibiting low-shear rate Newton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 0 publications
4
69
0
Order By: Relevance
“…The influence of plasticizer is more pronounced in the lower shear rate range whereas at higher shear rate its influence diminishes due to the shear thinning effect of the polymer melt. A master curve was produced using a concentration-dependent shift factor a c similar to Gerhardt et al [40]. The viscosity of CA plasticized with 15 wt % TEC was taken as the reference curve.…”
Section: Foam Extrusion Testsmentioning
confidence: 99%
“…The influence of plasticizer is more pronounced in the lower shear rate range whereas at higher shear rate its influence diminishes due to the shear thinning effect of the polymer melt. A master curve was produced using a concentration-dependent shift factor a c similar to Gerhardt et al [40]. The viscosity of CA plasticized with 15 wt % TEC was taken as the reference curve.…”
Section: Foam Extrusion Testsmentioning
confidence: 99%
“…The effects of CO 2 dissolution on viscoelastic properties were studied with capillary rheometers or extruders; for example, the shear rate dependence of viscosity was examined in the thinning regime. 1,2) These studies suggested that the dissolved CO 2 enhances the polymer chain motion (and effectively increase a distance from the glass transition point.) However, details of this effect on the linear viscoelastic relaxation and the equilibrium chain dynamics were not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the rheological and transport properties of solutions of polymer melts and physical blowing agents have attracted much attention. Accurate measurement techniques and determination of shift factors are the topics of several works [Han and Ma (1983a,b), Gerhardt et al (1997Gerhardt et al ( , 1998, Royer et al (2000Royer et al ( , 2001Royer et al ( , 2002, Kwag et al (1999), Lee et al (1999), Areerat et al (2002), ]. In most experimental studies (e.g., in measurements using capillary rheometry), the authors focused on the stationary viscosity of the melt as a function of the concentration of the blowing agent.…”
Section: Introductionmentioning
confidence: 99%